OPTIMIZATION OF Agrobacterium-MEDIATED GENETIC TRANSFORMATION OF oshox4 GENE IN SATOIMO TARO (Colocasia esculenta var. antiquorum) - Febrina Ariyanti Ismail; Aris Tjahjoleksono; N Sri Hartati (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2022)
Satoimo (Colocasia esculenta var. antiquorum) can be considered as an alternative food to support food diversification. The aim of this research was to obtain an optimum condition of the genetic transformation method of Satoimo taro through Agrobacterium-mediated genetic transformation using binary vector harboring gene construct of oshox4 and hpt gene as a selectable marker to produce transgenic plants. Plant materials that were used in this study were meristem, root, leaf, petiole, and basal stem. Transformation procedures were carried out using three different co-cultivation periods (1, 2, and 3 days) and different optical densities of A. tumefaciens cells (0,5 and 0,7). Furthermore, callus induction was performed on MS medium containing 2.4-D, cefotaxime, hygromycin and then regenerated on MS medium containing thidiazuron and hygromycin. The putative transgenic plantlets were selected on MS medium containing hygromycin and analyzed using PCR. The results showed that putative transgenic plants derived from the basal stem could survive on a selection medium containing hygromycin and based on PCR analysis some of them contained the oshox4 and hpt genes. Satoimo (Colocasia esculenta var. antiquorum) dapat dijadikan sebagai alternatif pangan untuk mendukung penganekaragaman pangan. Tujuan penelitian ini adalah mendapatkan kondisi optimal untuk transformasi genetik talas Satoimo menggunakan gen oshox4 yang dimediasi oleh Agrobacterium tumefaciens. Transformasi genetik dilakukan dengan menggunakan vektor biner yang mengandung gen oshox4 dan gen hpt. Bahan tanaman yang digunakan dalam penelitian ini adalah meristem, akar, daun, tangkai daun dan pangkal batang talas Satoimo. Transformasi dilakukan dengan menggunakan tiga perlakuan waktu ko-kultivasi (1, 2, dan 3 hari) serta dua optical density (0,5 dan 0,7). Selanjutnya dilakukan induksi kalus pada media MS yang mengandung 2.4-D, cefotaksim, hogromisin dan diregenerasikan pada media MS yang mengandung thidiazuron dan higromisin. Plantlet putatif transgenik diseleksi menggunakan media MS yang mengandung higromisin serta dianalisis menggunakan PCR. Hasil penelitian menunjukkan bahwa tanaman putatif transgenik yang berasal dari pangkal batang dapat bertahan hidup pada media seleksi yang mengandung higromisin dan berdasarkan analisis PCR, beberapa di antaranya mengandung gen oshox4 dan gen hpt.